Effect of demineralized dentin matrix and chitosan of black soldier fly on osteoblast and osteoclast activity in post-extraction socket preservation: an experimental study - Waty, Marsela Umbar; Dewi, Renie Kumala; Taufiqurrahman, Irham; Nahzi, Muhammad Yanuar Ichrom; Huldani, Huldani; Ganesh, Rajendran (Universitas Padjadjaran, 2025)
Introduction: Alveolar bone remodeling is crucial because it represents a key component of oral rehabilitation. Dentin Demineralization Matrix (DDM) and chitosan Black Soldier Fly (BSF) pupae have osteoinductive and osteoconductive properties, influencing osteoblast and osteoclast activity. The objective of this study was to analyze the effectiveness of a combined gel of DDM and chitosan BSF pupae on osteoblast and osteoclast activity. Methods: Eighteen guinea pigs were divided into control (C) and treatment (T) groups. The mandibular left incisor was extracted, and in the C group, the socket was filled with polyethylene glycol (PEG) gel as a placebo, then sutured using non-absorbable silk. In the T group, the socket was applied with chitosan BSF pupae gel and DDM, then sutured with non-absorbable silk. The samples were euthanized on days 7, 14, and 21, followed by histological evaluation with Hematoxylin & Eosin (H&E). Data were analyzed using the Kruskal-Wallis test due to non-normal distribution. Results: There were significant increases in the number of osteoblasts and a decrease in the number of osteoclasts over time between days 7, 14, and 21. Kruskal-Wallis analysis showed a statistically significant difference (p=0.011, p<0.05). Conclusion: Application of a combined DDM and BSF-chitosan pupae enhanced osteoblastic activity while suppressing osteoclastic activity after tooth extraction. These findings indicate its potential as a biomaterial candidate for alveolar bone regeneration and future regenerative applications.